Filosofi Tri Kaya Parisudha Memoderasi Pengaruh Equity Sensitivity Dan Ethical Sensitivity Pada Perilaku Etis Auditor Badan Pemeriksa Keuangan Perwakilan Provinsi Bali - Eka Rustiana Dewi, I Gusti Putu (LPM IHDN Denpasar, 2019)
This Study aims to examine the effect of equity sensitivity and ethical sensitivity on auditor’s ethical behavior in Financial Audit Board of Republic Indonesia (BPK RI) Representatives of Bali Province, as well as to examine whether philosophy of tri kaya parisudha which is one of local wisdom found in Bali will be able to strengthen the effect of equity sensitivity and ethical sensitivity on auditor’s ethical behavior. The research conducted because of the phenomenon of bribery cases which were involving auditors of BPK and have added to the list of corruption cases in Indonesia. Data collection in the research using survey method with questionnaire and the sample are 45 auditors of BPK RI representatives of Bali Province. The result shows that equity sensitivity and ethical sensitivity have positive significant effect on auditor’s ethical behavior, while the philosophy of tri kaya parisudha has an ability to strengthen the effect of equity sensitivity and ethical sensitivity on auditor’s ethical behavior.